2017
DOI: 10.1016/j.pep.2017.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterization of a highly pure RNA polymerase holoenzyme from Mycobacterium tuberculosis

Abstract: Recent publications have shown that active RNA polymerase (RNAP) from Mycobacterium tuberculosis (MtbRNAP) can be produced by expressing all four subunits in a single recombinant Escherichia coli strain [1–3]. By reducing the number of plasmids and changing the codon usage of the Mtb genes in the co-expression system published by Banerjee et. al [1], we present a simplified, detailed and reproducible protocol for the purification of recombinant MtbRNAP containing the ω subunit. Moreover, we describe the format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…M. tuberculosis RNAP was prepared from cultures of E. coli strain BL21(DE3) (Invitrogen, Inc.) co-transformed with plasmids of pACYC Duet- rpoA-rpoD , pCDF- rpoZ and pET Duet- rpoB-rpoC , and purified as described with some modifications (39). Single colonies of the resulting transformants were used to inoculate 100 mL LB broth containing 35 μg/mL chloramphenicol, 100 μg/mL ampicillin, 50 μg/mL streptomycin, and cultures were incubated for 16 h at 37 °C with shaking.…”
Section: Methodsmentioning
confidence: 99%
“…M. tuberculosis RNAP was prepared from cultures of E. coli strain BL21(DE3) (Invitrogen, Inc.) co-transformed with plasmids of pACYC Duet- rpoA-rpoD , pCDF- rpoZ and pET Duet- rpoB-rpoC , and purified as described with some modifications (39). Single colonies of the resulting transformants were used to inoculate 100 mL LB broth containing 35 μg/mL chloramphenicol, 100 μg/mL ampicillin, 50 μg/mL streptomycin, and cultures were incubated for 16 h at 37 °C with shaking.…”
Section: Methodsmentioning
confidence: 99%
“…Although its homologs (RpoK and RPB6) are essential in archaea and eukaryotes (28), has been shown to be nonessential in several bacteria (29)(30)(31)(32). In M. tuberculosis, the roles of have not been clearly investigated (33)(34)(35). In this study, we showed that the subunit is essential for the assembly of M. tuberculosis RNAP core and have characterized a loop region in M. tuberculosis which is essential for its roles.…”
Section: Discussionmentioning
confidence: 74%
“…We observed that deleting the N-terminal fourteen residues involved in domain-swapping in CarD results in loss of self-association to form SDS-resistant higher order oligomers and hampers its ability to form amyloids in solution. Though in our solution studies we did not observe monomeric form of CarD under tested concentrations, Asmat et al ., 52 have reported a small population of monomeric CarD in gel filtration experiments. The crystal structure of 1:1 stoichiometric complex of Mtb RNAP β1β2/CarD complex suggests that CarD exists as monomer as well in solution 18 .…”
Section: Discussionmentioning
confidence: 99%